O impacto da melhoria de um processo operacional na lucratividade e competitividade: um estudo de caso na subsidiária brasileira de uma empresa do ramo de petróleo - Scheiner, Patrick (2015)
Since the end of the 90's, after a sequence of economic cycles in Brazil, the country witnesses the opening of the oil industry, linked to the discovery of the pre-salt and the immeasurable volume of natural reserves. This milestone may mark the beginning of one of the most important and diversified industrialization cycles in Brazil's economic history. Even in this industry, a market of giants, multinational corporations, big players with innovative and irreplaceable know how's, is a well known fact, especially within the professionals of this area, that many oil companies have numerous critical basic factors with urgent need of improvement. The main objective of this dissertation is to make initially a brief strategic and market analysis of the Brazilian subsidiary of an oil and gas multinational group specialized in drilling fluids technologies with presence in more than twenty countries. After immersion on this context, realize a detailed analysis of an specific process, at first glance without importance, that after being studied, monitored and mapped, could be adjusted, redesigned and implemented, bringing vast gains to the corporation regarding profitability and competitive edge.